Driving SMESs Brand Equity Through Digital Marketing and Social Media Interaction Excellence - Muhammad Iqbal Baihaqi; Restu Akbar Suryaman (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2026)
This study examines the influence of digital marketing strategies, social media usage, and customer interaction on brand equity, with brand image as a mediating variable among MSMEs in Bandung City. A quantitative approach using Partial Least Squares (PLS) was employed, with data collected through questionnaires distributed to MSME owners and managers utilizing digital platforms. The findings indicate that digital marketing strategies, social media usage, and customer interaction have a significant effect on both brand image and brand equity. Furthermore, brand image is proven to mediate these relationships, thereby strengthening the sustainable competitive advantage of MSMEs. The novelty of this study lies in the simultaneous integration of the three key variables within a single empirical model, positioning brand image as a central mediating construct in the context of digitally oriented MSMEs at the local level, which remains underexplored in prior studies.